Human intestinal parasites on body surfaces of cockroaches at Universiti Sains Malaysia (USM) Health Campus - Sabri, Siti Umi Sahirah Mohd (Universiti Sains Malaysia, 2016)
In developed countries, human intestinal parasites are often neglected by the communities. This study aimed to screen for human intestinal parasites found on body surfaces of cockroaches at Desasiswa Nurani hostel USM Health Campus, Kubang Kerian, Kelantan. A total of 127 cockroaches were caught at four different locations using modified empty jar, commercial cockroach trap and hand gloves. Between the two species of cockroaches, the dominant species was Periplaneta americana (125/127; 98.4%) followed by Blattella germanica (2/127; 1.6%). Four or five cockroaches were grouped in each 50 ml tube to obtain a total of 26 groups. A solution of 0.9% normal saline was used to dislodge the parasites from body surfaces of the cockroaches by using vortex. After removing the cockroaches, the solution was centrifuged to obtain the pellet, which was then stained separately with trichrome or modified acid-fast stain. Subsequently, the parasites were screened using a light microscope under low and high magnification. In addition, DNA detection of Entamoeba histolytica was performed using an in-house duplex polymerase chain reaction (PCR) assay. The assay was incorporated with Plasmodium falciparum gene as the internal control to rule out false negative results. The microscopy results showed that neither helminth ova and larva nor protozoa cysts and trophozoites were observed in the samples. However, 34.6% (9/26) groups of cockroaches were found to harbour Strongyloides stercoralis. Interestingly, PCR analysis revealed that all the samples were negative for E. histolytica. In conclusion, neither helminth ova nor protozoa cyst or trophozoite were found in the samples. However, some samples contained rhabditiform larvae and free-living adult of S. stercoralis.